2020
DOI: 10.1111/aogs.13967
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ attitudes towards termination of pregnancy at viable stage

Abstract: Introduction Upon prenatal diagnosis of congenital malformations, termination of pregnancy (TOP) may be an option, sometimes at a gestational age when the fetus is already viable (late TOP). We aimed to study attitudes towards late TOP of all tertiary healthcare professionals involved in late TOP practice. Material and methods A mail survey was conducted among all physicians and paramedical professionals involved in late TOP decision‐making in all eight centers with a Neonatal Intensive Care Unit in Flanders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Palliative care and/or nonaggressive obstetric management is considered only as an option when neonatal death is inevitable within a reasonable time and/or parents prefer palliative care for their child 36 . We have already demonstrated that this option is less preferred by physicians than by paramedical professionals 37 . In 16% of all late TOPs in this study, no prenatal intervention to achieve foetal demise was taken, some of them beyond 26 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Palliative care and/or nonaggressive obstetric management is considered only as an option when neonatal death is inevitable within a reasonable time and/or parents prefer palliative care for their child 36 . We have already demonstrated that this option is less preferred by physicians than by paramedical professionals 37 . In 16% of all late TOPs in this study, no prenatal intervention to achieve foetal demise was taken, some of them beyond 26 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 70%
“…36 We have already demonstrated that this option is less preferred by physicians than by paramedical professionals. 37 In 16% of all late TOPs in this study, no prenatal intervention to achieve foetal demise was taken, some of them beyond 26 weeks of pregnancy. However, no foetus showed signs of viability after birth and no postnatal intervention was required.…”
Section: Infants Whose Stillbirth Was Preceded By Topmentioning
confidence: 89%
“…In einer Vergleichsstudie von Janvier et al zeigte sich beispielsweise, dass pädiatrische Assistenzärzte seltener einen Schwangerschaftsabbruch bei fetalen Fehlbildungen als ihre geburtshilflichen Kollegen in Betracht zogen 11 . Roets et al stellte in einer Befragung unter Ärzten und Pflegepersonal heraus, dass Ärzte wiederum im Falle von nicht-letalen Fehlbildungen häufiger als die anderen Berufsgruppen einen Fetozid einer neonatalen Palliativbehandlung vorziehen würden 12 . Crowe et al zeigten in einer Befragung unter Ärzten und Sozialarbeitern hinsichtlich der Beurteilung von Schwangerschaftsabbrüchen bei Feten mit schweren angeborenen Fehlbildungen deutlich unterschiedliche professionsbezogene Perspektiven auf ein behindertes Kind und die Folgen seiner Erkrankung.…”
Section: Diskussionunclassified
“…Feticide is therefore carried out to avoid this by inducing fetal demise in the uterus before TOP. Feticide is also often preferred to live birth, followed by neonatal palliative care by parents and healthcare staff involved in terminations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%